Discussion Lines on Gender and Transitional Justice: An Introductory Essay Reflecting on the ICTJ Bellagio Workshop on Gender and Transitional Justice - Nesiah, Vasuki (Columbia Journal of Gender and Law, 2006)
Feminist interventions have challenged the field of transitional justice, developed approaches, and formulated critiques that have revisited many foundational assumptions regarding the human rights canon and the role of legal processes, truth commissions, and other institutions in advancing justice struggles. In some areas feminist interventions in practice and scholarship had gained wider recognition and influenced developments in the field. However, in many other areas, feminist interventions have remained on the margins, with little discussion occurring even among feminists. It was in this context that the ICTJ gender program sought to convene a seminar that would take stock of feminist approaches in the field of transitional justice thus far while also providing a forum for considering how feminist critical inquiry may continue to transform the intellectual boundaries and settled practices of the field. It was also a seminar for debating differences among feminists regarding political priorities and strategies. The discussion was structured around the four commissioned pre-circulated papers on ideas of “victimization,” “truth,” “justice,” and “political violence” that are published in this volume. Each of the paper presentations and subsequent discussions addressed the conceptual assumptions behind transitional justice approaches in countries as diverse as India, Australia, South Africa, and Northern Ireland, foregrounding critical debates about what is at stake in transitional justice for feminists, and considering what “engendering” transitional justice actually means. Creating and fostering a space for constructive debate and engendering a critically reflective practice presented provocative challenges in both the planning process and the unfolding of the seminar itself. We questioned whether to engage with the canon by structuring discussion against the received precepts of ‘transitional justice’, or to use a different starting point that would not re-inscribe the field’s constitutive assumptions in contesting them. For instance, practitioners and scholars may often refer to the “pillars” of transitional justice: prosecutions, truth commissions (TRCs), reparations, institutional reform, and reconciliation initiatives. These are the established institutional avenues that structure and shape the conceptual imagination of the field, and ground its normative vision through institutions and practices. In organizing this seminar, however, we chose not to structure the discussion around these pillars, in hopes of launching a discussion that would allow us to revisit the boundaries of transitional justice.